Integration of morphological features and contextual weightage using monotonic chunk attention for part of speech tagging - Mundotiya R.K.; Mehta A.; Baruah R.; Singh A.K. (My University, 2025)
Part-of-Speech (POS) tagging is a fundamental sequence labeling problem in Natural Language Processing. Recent deep learning sequential models combine the forward and backward word informatio for POS tagging. The information of contextual words to the current word play a vital role in capturing the non-continuous relationship. We have proposed Monotonic chunk-wise attention with CNN-GRU-Softmax (MCCGS), a deep learning architecture that adheres to these essential information. This architecture consists of Input Encoder (IE), encodes word and character-level, Contextual Encoder (CE), assigns the weightage to adjacent word and Disambiguator (D), which resolves intra-label dependencies as core components. Moreover, different morphological features have been integrated into the core components of MCCGS architecture as MCCGS-IE, MCCGS-CE and MCCGS-D. The MCCGS architecture is validated on the 21 languages from Universal Dependency (UD) treebank. The state-of-the-art models, Type constraints, Retrofitting, Distant Supervision from Disparate Sources and Position-aware Self Attention, MCCGS and its variants such as MCCGS-IE, MCCGS-CE and MCCGS-D are obtained mean accuracy 83.65%, 81.29%, 84.10%, 90.18%, 90.40%, 91.40%, 90.90%, 92.30%, respectively. The proposed model architecture provides state-of-the-art accuracy on the low resource languages as Marathi (93.58%), Tamil (87.50%), Telugu (96.69%) and Sanskrit (97.28%) from UD treebank and Hindi (95.64%) and Urdu (87.47%) from Hindi-Urdu multi-representational treebank. © 2021 The Authors